Spammer Detection Prediction and Identification by ML - Manoj, Challapalli; Tejaswi, Talluru; Sandeep, M.; Ganesan, Vithya; Ramaswamy, Viswanathan; Chandan, Seelam; Akilan, T. (2022 4th International Conference on Advances in Computing, Communication Control and Networking (ICAC3N), 2022)
Social networking platforms are used by millions of individuals all around the world. The effects of user interaction with social networking sites like Twitter and Facebook, which are both influential and unpopular in everyday life, are both influential and unpopular. Spammers have turned to well-known social networking sites to disseminate a significant volume of useless and delete able content. For example, Twitter has grown to become one of the most frequently utilized platforms of all time, allowing for a fictitious spam level. Spam detection and false identity detection on Twitter have recently been frequent study topics on modern online social networks (OSNs). We conduct a strategic evaluation in this study to identify persons who publish spam on Twitter. Furthermore, the group of Twitter spam detection algorithms divides them into categories depending on their capacity to trace false content, spam-based URLs, spam on popular subjects, and phone users. The methodologies are also contrasted in terms of other characteristics, such as user, content, graph, layout, and time characteristics. Unwanted tweets by fraudulent users disrupts authorized customers and impedes resource usages. Additionally, the potential to distribute information about phone identities to users has grown, leading in the distribution of inappropriate content.